Assessment of the SISCO SV Academic Stress Inventory adapted to the context of COVID-19 in a Peruvian university population - Alania-Contreras, Rubén Darío (2021)
The objective of the study was to measure the SISCO SV Academic Stress Inventory adapted to the context of the COVID-19 crisis, the instrumental research was of quantitative approach, basic type, descriptive level and non-experimental, cross-sectional, simple descriptive design. The participants were 974 university students from the Junín region, to whom the inventory was applied online. The instrument was validated under construct evidence with the corrected Pearson's r correlation coefficient and confirmatory factor analysis; reliability was excellent, evaluated with Cronbach's alpha internal consistency coefficient (0.946); the scale was established based on the uniform statistical distribution with three equiprobable categories: mild (0-78), moderate (79-157) and severe (158-235). In conclusion, the SISCO SV academic stress inventory, adapted to the context of the crisis by COVID-19, was successfully barcoded, which will allow measuring and interpreting the academic stress levels of the university student population.